Direct Observation of Orbital Driven Strong Interlayer Coupling in Puckered Two‐Dimensional PdSe2 (Small 9/2022). Issue 9 (3rd March 2022) - Ryu, Jung Hyun; Kim, Jeong‐Gyu; Kim, Bongjae; Kim, Kyoo; Kim, Sooran; Park, Jae‐Hoon; Park, Byeong‐Gyu; Kim, Younghak; Ko, Kyung‐Tae; Lee, Kimoon
Abstract : Interlayer Coupling In article number 2106053, Kyung‐Tae Ko, Kimoon Lee, and co‐workers unveil the crucial role of the Pd 4 d orbital distribution on the strong interlayer interaction, which is attributed to the combined effect of local symmetry and unique occupancy. The cover image illustrates that there exists a strong degree of interlayer interaction in 2D PdSe2 originating from the directional orbitals even under a large interlayer distance.